PENURUNAN WAKTU PRE DELIVERY INSPECTION DI AHASS SEPEDA MOTOR HONDA PT EKA PRIMA MANDIRI SENTOSA SURABAYA - Franklyn Tanuwijaya; Joni Dewanto (Petra Christian University, 2016)
PT Eka Prima Mandiri Sentosa Surabaya is one of the authorized workshops for Hondamotorcycle or commonly referred to as AHASS (Astra Honda Authorised Service Station). As acompany engaged in services, AHASS should be able to give satisfaction to be services. Eachmotorcycle unit issued by PT Eka Prima Mandiri Sentosa Surabaya, shall be carried out variouschecks and tests PDI. Observations indicate that the travel time of the PDI during takes > 30minutes. It is, indicates that the travel time of workmanship PDI is considered less effective andbe the one that causes delays in delivery, and lead to reduced consumer satisfaction. The finaltask was created with the aim to: 1) improve the speed in which the original PDI system theaverage time it takes > 30 minutes, the expected program running process can be finished within20 minutes; 2) to increase the capacity of PDI motorcycle 17 units per day. Based on the study ofliterature and the process of apprenticeship by the Author, due to workmanship is not designedwith the standard operating procedure (SOP) was good, and the absence of check list to makethe stages through which is not according to the SOP which eventually phases may pass and notappropriate check list. To that end, the author offers some solutions: 1) the design of a specialSOP PDI; 2) a draft checklist PDI; 3) design layouts room PDI; 4) the layout and Mechanicstoolbox.